2010
DOI: 10.1111/j.1365-2672.2009.04565.x
|View full text |Cite
|
Sign up to set email alerts
|

Production of enterocin A byEnterococcus faeciumMMRA isolated from ‘Rayeb’, a traditional Tunisian dairy beverage

Abstract: Aims:  Characterization and purification of a bacteriocin produced by a wild Enterococcus faecium strain, isolated from a Tunisian traditional fermented milk. Methods and Results:  Enterococcus faecium MMRA was selected on the basis of its strong anti‐Listeria activity. The antibacterial activity was sensitive to proteases, confirming its proteinaceous nature. It was extremely heat stable (15 min at 121°C), remained active over a wide pH range (2–12), and also after treatment with lipase, amylase, organic solv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0
3

Year Published

2011
2011
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 48 publications
1
27
0
3
Order By: Relevance
“…and Enterococcus spp. [14,30,53]. Nisin usually retains its antimicrobial activity when exposed to a variety of pH levels and is capable of displaying the highest inhibitory activity at low pH; when the pH is lowered, the solubility and stability of nisin tend to increase [11,17,19,22,42,12].…”
Section: Bacteriocinogenic Activitymentioning
confidence: 99%
“…and Enterococcus spp. [14,30,53]. Nisin usually retains its antimicrobial activity when exposed to a variety of pH levels and is capable of displaying the highest inhibitory activity at low pH; when the pH is lowered, the solubility and stability of nisin tend to increase [11,17,19,22,42,12].…”
Section: Bacteriocinogenic Activitymentioning
confidence: 99%
“…That no activity was shown against Gram-negative bacteria may be due to the relative impermeability of their outer membranes (Jack et al, 1995). Rehaiem et al (2009) reported that CS of Ent. faecium MMRA could inhibit Lactobacillus, Leuconostoc, Enterococcus, and Listeria species, but there was no inhibition of Gram-negative bacteria, Hafnia, Serratia, and E. coli.…”
Section: Effect Of Antibacterial Activity Of Bls Against Bacterial Inmentioning
confidence: 99%
“…A decrease in the bacteriocin activity has also been observed for bacteriocins produced by Ent. faecium MMRA (Rehaiem et al, 2009), Leuconostoc mesenteroides E131 (Xiraphi et al, 2008), and Lb. acidophilus (Karthikeyan and Santhosh, 2009).…”
Section: Growth Curve and Bls Production From Ent Faecium Ce5-1mentioning
confidence: 99%
See 1 more Smart Citation
“…Rayeb, produced by spontaneous fermentation of raw milk at ambient temperature for a period of 24 h to 72 h, has nutritional benefits and plays an important role in the population diet, particularly those of rural population (Idoui et al, 2010). Mixed species of lactic acid bacteria (LAB), Leuconostoc, enterococci, yeasts, especially species of the genera Saccharomyces and Candida as well as moulds are responsible of spontaneous fermentation (Rehaiem et al, 2010). Dwing to their proteolytic and lipolytic activities, yeasts represent a significant part in flavoring properties by producing volatile compounds and inducing organoleptic characteristics of Mediterranean areas-fermented milk .…”
Section: Introductionmentioning
confidence: 99%